Subplatysmal Flap Reconstruction After Hemiglossectomy and Radical Neck Dissection for Tongue Squamous Cell Carcinoma in low-resource settings - Fahreza Syukri; Muhammad Zaki Abdul Hafiz; Andrea Valentino; Effif Syofra Tripriadi; Fathar Usman Bunawir; Muhammad Salamullah; Sinta Chaira Maulanisa (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Squamous cell carcinoma (SCC) of the tongue exhibits aggressive local behavior and a high propensity for early cervical lymphatic metastasis. The routine management of locally advanced disease consists of hemiglossectomy with radical neck dissection followed by primary reconstruction. In many low-resource settings, microvascular free flaps may not be feasible due to limited infrastructure, prolonged operative times, or patient comorbidities. The subplatysmal flap offers a practical, time-efficient alternative in such circumstances. Case Presentation: We report a 71-year-old male with stage T3N2bM0 tongue SCC who underwent hemiglossectomy and ipsilateral RND, followed by immediate reconstruction using a subplatysmal flap harvested from the anterior cervical triangle. The flap provided adequate coverage, excellent viability, and satisfactory functional recovery, with no major postoperative complications. Conclusion: The subplatysmal flap is relatively safe and oncologically acceptable as well as functionally efficient method for moderate-size tongue defect, especially for older age or comorbid patient and non-microsurgical center.